The S-O-R Approach to Analyzing Comparative Effectiveness of Influencer Marketing and Social Media Ads: The Mediating Roles of Brand Awareness and Perceived Value on Consumer Purchase Intention - Wawan Kurniawan; Yolanda Masnita; Kurniawati (Universitas KH. Abdul Chalim Mojokerto, 2026)
The exponential growth of social media has established influencer marketing and paid advertising as dominant promotional channels, yet a critical knowledge gap persists regarding their comparative effectiveness when brands deploy both strategies concurrently. Prior research predominantly examines these channels separately, failing to address the practical reality brands face in allocating resources across simultaneous campaigns. This study fills this void using the Stimulus-Organism-Response (S-O-R) theoretical lens to assess comparative effectiveness of influencer marketing versus social media ads on purchase intention, mediated through brand awareness and perceived value. Analysis incorporated responses from 270 active social media users recently exposed to both promotional formats within 3-6 months. Employing PLS-SEM methodology, six hypotheses were examined: two testing direct relationships (H1-H2) and four assessing mediation mechanisms (H3-H6). Results provide empirical validation across all hypotheses. Influencer marketing exhibits superior direct impact on purchase intention, while social media advertising achieves greater effectiveness via indirect routes, especially through enhanced brand awareness and value perception formation. This research advances literature by delivering the inaugural comparative examination of concurrent marketing stimuli within an integrated analytical structure, revealing how consumers mentally process simultaneous promotional communications. For practitioners, findings inform strategic decisions regarding resource distribution and the construction of cohesive communication approaches capitalizing on each channel's distinct advantages.